Qualidade de produtos lácteos fermentados produzidos no estado da Paraíba - Brasileiro, Jéssica Lisana Ouriques (2014)
Yogurt and fermented milk beverages are fermented dairy products that have increased consumption worldwide, and the demand for functional foods spurred the expansion of these products. Thus, it was entended to evaluate the quality of fermented dairy foods produced in the state of Paraíba. Samples of yogurts and milk beverages of the four mesoregions of the state with federal or state registration were performed, the drinks were evaluated on their labeling, microbiological, physical, chemical and rheological properties. Observing the labels, it was found that 89% were in compliance with the legislation, the main irregularities detected were: unauthorized use of additives in the Technical Regulations and the illegibility of the dates of manufacture and validity, which puts at risk consumer health. Although there has been growth of molds and yeasts, 91% of the samples were within the microbiological parameters determined by current legislation. The centesimal composition varied depending on the mesoregion and inspection record. The rheological behavior varied between samples. Was observed relationship between physico-chemical parameters (total solids and protein) and the apparent viscosity. Overall, yogurts and fermented dairy beverages showed satisfactory quality, but should improve labeling requirements, standards of identity and sanitary quality in order to not endanger consumers health, satisfy the increasingly demanding market and to compete with major brands.